ANALISIS POLA DAN EFEKTIVITAS TERAPI ANTIBIOTIK EMPIRIS TERHADAP PERBAIKAN KLINIS PADA PASIEN KERATITIS BAKTERIAL RAWAT JALAN - Widya Ari Sandi; Seftika Sari; Neni Frimayanti (Journal Pharma Saintika, 2025)
Abstract. Bacterial keratitis is a corneal infection that may lead to pain, visual impairment, and even permanent blindness if not promptly and appropriately treated. In outpatient settings, empirical antibiotic therapy is often chosen as the initial management because culture and sensitivity results require more time, whereas delays in therapy may worsen the clinical condition. This study aims to evaluate the effectiveness of empirical antibiotic therapy on clinical improvement and follow-up visits in patients with bacterial keratitis. A systematic literature review was conducted by searching PubMed and Google Scholar for articles published between 2015 and 2025. From 242 articles identified, 12 met the inclusion criteria and were analyzed further. The findings revealed that moxifloxacin and ciprofloxacin were the most frequently prescribed topical antibiotics, with treatment durations ranging from 7 to 21 days. Overall, empirical therapy was shown to accelerate clinical improvement, particularly within the first week of treatment. However, evidence supporting a reduction in follow-up visit frequency remains limited and presents varied results across studies, potentially due to differences in study design and patient conditions. Factors such as treatment regimen, duration of therapy, disease severity, and patient characteristics were also reported to influence the variability in outcomes. In conclusion, empirical antibiotic therapy appears to be clinically effective for bacterial keratitis. Nevertheless, to obtain a more comprehensive understanding of its impact on follow-up visits and implications for outpatient services in Indonesia, further research with larger sample sizes and prospective study designs is required.